Detection and Identification of Some Organic Compounds in Sewage Samples by FTIR and GLC-MS - Wagh, S.P.; Shrivastava, V.S. (Asian Journal of Chemistry, 2010)
The organic compounds were identified in some sewage samples, which were taken from Someshwar and Tapovan at Nasik. These samples were extracted with the CH2Cl2 and characterized by FTIR and GC-MS. The identified organic compounds are saturated and unsaturated hydrocarbons, aromatic alcohols, phenols and dicarboxylic acids that affect adversely the soil and ground water quality of the area.